Peran Pemerintah Desa dalam Pengembangan Ekowisata Danau Jemelak - Nikodimus Nikodimus; Gradila Apriani; Petrus Atong (Universitas Musamus, Merauke, Papua, 2020)
Ecotourism is part of a sustainable development which focusing in empowerment of local people. Therole of Village government as the spearhead of development is indispensable in the development ofecotourism. This research was aim to understand the perception, infrastructure management and policyof Jerora Satu village Sintang Subdistrict Sintang Regency West Kalimantan Province in support thedevelopment of Jemelak Lake Ecotourism. Qualitative descriptive method was used in this research. Datais gathered through questionnaire, in-depth interview, and documentation. Data analysis used descriptiveanalysis technic. The results shows that perception from the government of Jerora Satu village aboutJemelak Lake ecotourism is in medium level (38,1% = doubt) but in the other way they believe thatecotourism can be the potential village income in the future. Infrastructure development in supportJemelak Lake Ecotourism is still absence but through collaboration of many stakeholders its can be fitup the needs of Eco tourist which visit there. Village policy in support Jemelak Lake ecotourism is stilllack but traditional rules (aturan adat) is a good foundation to maintain the Jemelak Lake ecosystem tobecome the ecotourism destination. Village government is still on the move to campaign the local peopleto protect their environment which potential as their extra income in future through ecotourism.